Clindamycin phosphate 1.2% / tretinoin 0.025%: a novel fixed‐dose combination treatment for acne vulgaris. (June 2015) - Ochsendorf, F.
Abstract: The Global Alliance to Improve Outcomes in Acne Group recommends retinoid‐based combination therapy as first‐line therapy and the preferred treatment approach for almost all acne patients except those with the most severe disease. Clindamycin 1% (as clindamycin phosphate 1.2%)/tretinoin 0.025% (Clin‐RA) is a new fixed‐dose retinoid‐based combination therapy. The aqueous‐based gel formulation of Clin‐RA was designed to minimize skin irritation and optimize adherence with the therapy. It contains both solubilized and crystalline tretinoin which allows the retinoid to be slowly released onto the skin surface and decreases the potential for cutaneous irritation. A pooled analysis of three pivotal studies involving 4550 acne patients showed that Clin‐RA is well tolerated and effective at treating both inflammatory and non‐inflammatory acne lesions. The onset of action of Clin‐RA is rapid occurring within 2 weeks of treatment initiation. It is not associated with acne flaring or an increase in clindamycin‐resistant Propionibacterium acnes counts. Clin‐RA is considered as effective as adapalene 0.1%/benzoyl peroxide (BPO) 2.5%, whereas Clin‐RA has a more favourable tolerability profile. Clin‐RA may be more effective than clindamycin 1%/BPO 5% at treating non‐inflammatory acne lesions since the latter does not contain a retinoid to target comedones. Clin‐RA is also easy for patients to handle and apply, and has the advantage of not containing BPO which can bleach hair and fabrics. Taken together, the profile of Clin‐RA suggests Clin‐RA to be a first‐line treatment for patients with facial acne.